Positive Pressure Ventilation Treatment Based on Daytime and Night-time Titration in Patients with Obesity Hypoventilation Syndrome: A Randomized Controlled Trial - Babak Amra; Marzieh Ghasemi; Forogh Soltaninejad; Mehrzad Salmasi (Sleep Science, 2023)
Objectives The aim of the present study was to investigate the improvements of gas exchange and excessive daytime sleepiness in patients with obesity hypoventilation syndrome (OHS) in daytime and night-time split polysomnography (DSPSG and NSPSG).